Coconut Oil and Bees Wax Edible Coating for Postharvest Quality Maintenance of Bari Malta-1 at Ambient Storage: Coconut Oil and Beeswax Coating for Bari Malta-1 Quality - Nasrin, Taslima Ayesha Aktar; Rahman, Md Atiqur; Arfin, Most Sadia; Afroz, Mafruha; Molla, Mohammad Mainuddin; Sabuz, Ashfak Ahmed; Naznin, Most Tahera; Matin, Md Abdul (SAARC Journal of Agriculture, 2025)
An experiment was conducted to assess the influence of coconut oil and beeswax edible coating on the postharvest storage quality of Malta (Citrus sinensis) at ambient conditions (27±4°C and 65±5% RH). Sorted fruits were washed with drinking water; after removing surface water, fruits were coated with coconut oil and beeswax mixture (90:10 or 80:20 or 70:30) or only coconut oil. After coating, fruits were kept in crates and stored at 27±4°C and 65±5% RH. Weight loss, firmness, external colour (hue angle and lightness), TSS, pH, ascorbic acid, total sugar and reducing sugar were analyzed periodically during storage. After 18 days of storage, uncoated Malta had lost 45.6% of its firmness, while only coconut oil coated Malta had lost 32.7%, and combinations of coconut oil and beeswax Malta had lost just about 20%. The maximum weight loss of 16% was recorded in the uncoated Malta, whereas only 6% was lost in the Malta coated with a mixture of coconut oil beeswax (7:3) on the last day of storage. During the eighteenth day of storage, uncoated Malta retained 44.00 mg/100g of ascorbic acid, indicating a significant loss during storage. The levels of ascorbic acid in coated Malta that had either been coated with coconut oil alone or with coconut oil and beeswax on the final day (18) of storage ranged from 54 to 58 mg/100g. The findings showed that using coconut oil alone or in combination with a beeswax coating effectively maintained the ascorbic acid content, prevented weight loss, and maintained Malta's firmness throughout storage. SAARC J. Agric., 22(2): 275-287 (2024)